The effectiveness of EM4 addition in the biofilter tanks to reduce the nitrate and phosphate concentration in the Sago Industrial Liquid Waste - Asra Trigana Lisva; Sampe Harahap; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract The sago industrial liquid waste is rich in Nitrate and Phosphate and thus need to be processed before being flown to environment. A study aims to reduce the nitrate and phosphate in that sago liquid waste by using biofilter that was added with Effective Microorganisms-4has been conducted in April-May 2019. There were 3 treatments applied, namely the addition of 17 mL, 20 mL, and 23 mL EM4 in the anaerob tank and aerob tank. The waste was settled for 3 days in the anaerob tank and 3 days in the aerob tank. The treated waste was then tested for Nitrate and Phosphate concentrations. The treated waste was also used for rearing Osphronemus gouramy seedlings. Results shown that the Nitrate levels were reduced from 44.47 mg/L to 13.53 mg/L and the Phosphate levels were reduced from 1.0951 mg/L to 0.1372 mg/L. The best treatment to reduce the nitrate and phosphate concentrations was the addition of 20 mL EM4 and the survival rate of O.gouramy seedlings was 73%. It can be concluded that the addition of EM4 in the biofilter tanks was able to reduce the Nitrate and Phosphate concentration in the sago industrial liquid waste.Keyword : Effective Microorganisms-4, Osphronemus gouramy, Biofilters, Aerob tank, Anaerob tank